(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
يهدف هذا البحث إلى دراسة الصفات المورفولوجية لمجموعة من أصول الحمضيات المزروعة تحت الظروف البيئية للساحل السوري, والموجودة في المجمع الوراثي التابع لقسم بحوث الحمضيات في الهيئة العامة للبحوث العلمية الزراعية، والتي شملت الأوراق والأزهار والثمار، بالإضافة لاستخدام المعطيات الرقمية الناتجة في إنشاء مخطط القرابة الوراثية فيما بينها. بينت النتائج وجود عدد من الصفات الشكلية التي سمحت بتفريق الأصول عن بعضها ووضعها في مجموعات مستقلة، فقد تميزت الأصول سيتروميلو وسيترانج كاريزو والبرتقال ثلاثي الأوراق، بوجود الورقة المركبة (ثلاثية الوريقات)، مقابل الأصول الأخرى ذات الورقة البسيطة، في حين تميزت الأصول التابعة لمجموعة الحامض من خلال مواصفات الثمار، أما النارنج (الزفير) فقد تميز عن بقية الأصول بوجود الجناح على الأوراق، وبأزهاره الكبيرة الحجم، في حين لوحظ وجود الأزهار الصغيرة لدى الأصول التابعة لمجموعة المندرين، أما صفة تعدد الأجنة فقد تميزت بها بذور الأصول المدروسة كافة. The aim of this study was to study the morphological characteristics of some citrus rootstocks planted in the environmental condition of the Syrian coast especially in the gene pool of the Department of Citrus Research belonging to the General Organization for Agriculture Scientific Researches, using the morphological parameters of leaves, flowers and fruits. Results of the morphological analysis showed presence of some morphological characteristics which made it possible to distinguish between the different rootstocks and to cluster them in separate groups. The rootstock Citromelo, Carizo sitrange and the poncirus trifoliate were characterized by composite leaves (trifoliate), while the other rootstocks had leaves with simple form. The rootstocks of Lemon group were distinguished by the form of their fruits, while C. aurantium L. was characterized by the presence of wings on the leaves, and their big flowers. The small flowers characterized the rootstock of mandarin group. The phenomena of poly-embryos were observed in all citrus germplasms used in this study.